Validation Of Matching NIK, NPWP And Assistance In Filling Out Annual Tax - Adelia Octafia Nur Ramadhani; Sri Andriani (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
In Indonesia’s tax administration system, the integration of the National Identity Number (NIK) and the Taxpayer Identification Number (NPWP) is essential to ensure data accuracy, service efficiency, and improved taxpayer compliance. This study investigates the validation process of matching NIK and NPWP, as well as the need for assistance in completing the Annual Income Tax Return (SPT). A mixed-method approach was applied, combining quantitative bibliometric analysis using VOSviewer and qualitative literature review. The findings reveal a significant number of publications discussing the Tax Identification Number from 2019-2024, categorized into five main research clusters. The study proposes an assistance in SPT completion. Such a system is expected to minimize reporting errors and enhance voluntary taxpayer compliance in Indonesia’s digital tax administration.